2007
DOI: 10.1111/j.1558-5646.2007.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of a Key Floral Trait in Aquilegia Canadensis (Ranunculaceae): Genetic Variation in Herkogamy and Its Effect on the Mating System

Abstract: The mating system of flowering plant populations evolves through selection on genetically based phenotypic variation in floral traits. The physical separation of anthers and stigmas within flowers (herkogamy) is expected to be an important target of selection to limit self-fertilization. We investigated the pattern of phenotypic and genetic variation in herkogamy and its effect of selffertilization in a broad sample of natural populations of Aquilegia canadensis, a species that is highly selfing despite strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 72 publications
11
88
2
1
Order By: Relevance
“…In self-compatible species, herkogamy has been mainly proposed as a mechanism to limit selfing, but it also influences sexual interference between male and female floral functions (Barrett 2002). Herkogamy negatively affects seed set when pollinators are absent (e.g., Luijten et al 1999;Moeller 2006;de Vos et al 2012), and several genetic analyses confirmed the expected positive correlation between herkogamy and outcrossing rates, both among (e.g., Rick et al 1977;Holtsford and Ellstrand 1992;Luo and Widmer 2013) and within populations (e.g., Karron et al 1997;Brunet and Eckert 1998;Takebayashi et al 2006;Herlihy and Eckert 2007;Weber et al 2012; but see Medrano et al 2005Medrano et al , 2012. Importantly, herkogamy is known to decrease during anthesis in some species, potentially increasing opportunity for autonomous selfing in later stages of anthesis (Luijten et al 1999;Armbruster et al 2002;Duan et al 2010;de Vos et al 2012).…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…In self-compatible species, herkogamy has been mainly proposed as a mechanism to limit selfing, but it also influences sexual interference between male and female floral functions (Barrett 2002). Herkogamy negatively affects seed set when pollinators are absent (e.g., Luijten et al 1999;Moeller 2006;de Vos et al 2012), and several genetic analyses confirmed the expected positive correlation between herkogamy and outcrossing rates, both among (e.g., Rick et al 1977;Holtsford and Ellstrand 1992;Luo and Widmer 2013) and within populations (e.g., Karron et al 1997;Brunet and Eckert 1998;Takebayashi et al 2006;Herlihy and Eckert 2007;Weber et al 2012; but see Medrano et al 2005Medrano et al , 2012. Importantly, herkogamy is known to decrease during anthesis in some species, potentially increasing opportunity for autonomous selfing in later stages of anthesis (Luijten et al 1999;Armbruster et al 2002;Duan et al 2010;de Vos et al 2012).…”
Section: Introductionmentioning
confidence: 73%
“…The lack of a significant difference in the mean outcrossing rates of the two herkogamy classes is surprising for two reasons. First, most other studies that considered herkogamy variation among individuals found significantly diminished outcrossing in low-herkogamous individuals (e.g., Karron et al 1997;Brunet and Eckert 1998;Takebayashi et al 2006;Herlihy and Eckert 2007). Second, the absolute amount of herkogamy difference between classes was shown to greatly affect seed set under pollinator exclusion , demonstrating that the autonomous component of selfing is affected by herkogamy.…”
Section: Effects Of Herkogamy On Matingmentioning
confidence: 99%
See 3 more Smart Citations